Implication of G Protein-Coupled Receptor 43 in Intestinal Inflammation: A Mini-Review - Yang, Guan; Chen, Siyuan; Deng, Baichuan; Tan, Chengquan; Deng, Jinping; Zhu, Guoqiang; Yin, Yulong; Ren, Wenkai (Frontiers in Immunology, 2018)
Short chain fatty acids (SCFAs, e.g., acetate, propionate and butyrate) are a subset of fatty acids that are produced by gut microbiota during the fermentation of dietary fiber. Most beneficial roles of SCFAs in the gastrointestinal tract are mediated by directly activating its receptor, G-protein-coupled receptor 43 (GPR43, also known as FFAR2). Various recent studies have demonstrated the role of GPR43 in intestinal inflammatory diseases, such as inflammatory bowel diseases. Therefore, GPR43 could potentially be a drug target for intestinal inflammatory diseases. In this review, we review the current knowledge on the regulatory mechanisms associated with GPR43 in intestinal inflammation.